Bioakumulasi Timbal (Pb) Pada Makroalga Padina australis Hauck Di Perairan Laut Kota Makassar, Sulawesi Selatan - Supardi, Wahyu; Nugroho, Andika Puspito (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2019)
Pb lead metal is one of marine pollution material that can accumulate on macroalga Padina australis. The purpose of this research is to know the accumulation of Pb on P.australis, the abundance, and to know the Pb content correlation with abundance on P. australis. Research conducted on February 2018 in Makassar marine waters. The results indicate that there is a difference of the metal content of Pb on P.australis in each station. The metal content of Pb on the station I was at the range 0,0964-0,1388 ppm, Station II 0,0496-0,1050 ppm, and Station III 0,0597-0,1035 ppm which has exceeded the waters standard limit set>0.008 ppm.Â The high average Pb concentration on the station I because the station I was closer to the mainland of potentially greater influx of Pb heavy metals on macroalgae. P. australis abundance on a station I 92 individuals, II 152 individuals, and III 319 individuals. The data analysis result shows the value of significant correlations 0.384>0.05 that there is no correlation between the Pb concentrations with abundance but the direction of correlation indicates negative (-0331) which means that if the Pb concentration rises thenÂ P. australis abundance will decrease.